How Self‐Regulation Creates Distinct Values: The Case of Promotion and Prevention Decision Making - Higgins, E. Tory (Journal of Consumer Psychology, 2002)
I propose that different relations among basic components of self‐regulation produce distinct types of decision value: (a) Outcome value is produced when the consequences of a decision are relevant to the regulatory orientation of the decision maker, (b) value from fit is produced when goal pursuit means suit the regulatory orientation of the decision maker, and (c) value from proper means is produced when goal pursuit means are in agreement with established rules and normative principles. I use the regulatory focus distinction between promotion focus concerns with aspirations and accomplishments and prevention focus concerns with safety and responsibilities (Higgins, 1997, 1998) to illustrate outcome value and value from fit. Justification of a decision is used to illustrate value from proper means. I propose that decision makers are unlikely to distinguish among their experiences of these 3 types of value, and thus value from fit and value from proper means can be transferred to outcome value. I present evidence of such value transfer and consider its implications for value to the customer. I also reconsider sunk costs and the endowment effect in light of there being value beyond outcome value.